Militares e política no Brasil - Antonio Jorge Ramalho da Rocha (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This chapter argues that notwithstanding the recent improvements, the Brazilian society has still much to do to strengthen its institutions and to enhance the quality of its democracy concerning the regulation of security and defense. It examines historical aspects pertaining civil-military relations in Brazil and discusses key values in the formation of the military from a civilian standpoint. It also focuses on the transition to democracy from the most recent authoritarian period (1964-1985), which is still to be properly evaluated in terms of its achievements and errors. It further examines institutional innovations such as the National Defense Strategy, which despite its shortcomings constitutes a significant step forward. Finally, the argument favors greater involvement of the Brazilian society, particularly through the Legislative Power, in the decisionmaking process concerning security and defense issues.
Keywords: N46; Z13; 330